Structural and Electrical Properties of Graphene Oxide-Doped PVA/PVP Blend Nanocomposite Polymer Films - S. K. Shahenoor Basha; K. Vijay Kumar; G. Sunita Sundari; M. C. Rao (Advances in Materials Science and Engineering)
Graphene oxide (GO) nanoparticles were incorporated in PVA/PVP blend polymers for the preparation of nanocomposite polymer films by the solution cast technique. XRD, FTIR, DSC, SEM, and UV-visible studies were performed on the prepared nanocomposite polymer films. XRD revealed the amorphous nature of the prepared films. Thermal analysis of the nanocomposite polymer films was analyzed by DSC. SEM revealed the morphological features and the degree of roughness of the samples. DC conductivity studies were under taken on the samples, and the conductivity was found to be 6.13 × 10−4 S·cm−1 for the polymer film prepared at room temperature. A solid-state battery has been fabricated with the chemical composition of Mg+/(PVA/PVP  :  GO)/(I2 + C + electrolyte), and its cell parameters like power density and current density were calculated.